5PSQ-009 Patient safety and medication safety culture in a hospital pharmacy department: a mixed-methods study. (23rd March 2022) - Mc Namara, G; Gleeson, L; Harnett, A
Abstract : Background and importance: Pharmacists play an essential role in patient safety culture and medication safety, coordinating and implementing patient safety initiatives and preventing medication errors; however, there is limited literature on safety culture in pharmacy departments specifically. While patient safety culture surveys are a widely accepted measurement tool to measure patient safety culture, there is no widely used tool to measure attitudes towards medication safety. Measuring patient and medication safety culture could identify important areas for improvement. Aim and objectives: To assess the perceptions, opinions and attitudes of pharmacy staff to the patient and medication safety culture in a hospital pharmacy department. Material and methods: A mixed-methods cross-sectional survey study was conducted in a hospital pharmacy department over a 2-week period in June 2021. The quantitative phase involved a patient safety culture assessment, using an adapted version of the Safety Attitudes Questionnaire (SAQ) and a medication safety culture assessment with 12 Likert-scaled questions developed by the research team. Statistical analysis was performed on the quantitative data. Qualitative data from two open-ended questions on recommendations to improve patient and medication safety were subjected to thematic analysis. Results: Forty-four staff members completed the questionnaire (30 pharmacists and 14 pharmacy technicians) resulting in a 75.9% response rate. The pharmacy department scored below the SAQ international benchmark in four domains, with particularly low scores in the 'Perception of Management' and 'Working Conditions' domains. Medication safety culture scores were positive with a mean score of 61.8. Seven themes emerged from the qualitative data: (1) Communication, (2) Staffing Issues, (3) Training and Education, (4) Digital and Technological Advances, (5) Environment, (6) Collaboration and (7) Medication Safety Initiatives. Conclusion and relevance: Survey respondents identified many barriers to improving safety in the hospital including staffing issues, communication, lack of training and education and work environment. Pharmacy staff recommended the use of more technological advances, collaboration with multidisciplinary teams and more medication safety initiatives. These are important recommendations which should be discussed with hospital management and introduced to improve the safety culture in the hospital. References and/or acknowledgements: Conflict of interest: No conflict of interest